Health care professionals’ perception of contraindications for physical activity during cancer treatment - Tsiouris, Angeliki; Ungar, Nadine; Sieverding, Monika; Steindorf, Karen; Wiskemann, Joachim (Frontiers in oncology, 2018)
Introduction: Suggested medical contraindications for physical activity during cancer therapy might have an influence on physical activity recommendation behavior of Health Care Professionals. The purpose of the present study was to examine perceptions of physicians and oncology nurses towards specific medical conditions as contraindications for PA during cancer treatment. Materials and Methods: A total of 539 physicians and 386 oncology nurses were enrolled in this cross-sectional survey. Health Care Professionals judged thirteen medical conditions as to whether they are contraindications for physical activity during cancer treatment. Answering format was “no contraindication” / “potentially a contraindication” / “yes, a contraindication”. Results: Chi-square analyses revealed significant differences between general practitioners, specialized physicians and oncology nurses in their perception of ten medical conditions. Approximately half of the medical conditions were answered cautiously, showing high numbers on the response option potentially (36% - 72%). Moreover, physicians’ ratings differed significantly depending on their practical experience with particular medical conditions. Those being familiar with a specific medical condition were more permissive to physical activity during treatment, with effect sizes (Cramer’s V) ranging from .13 to .27. Conclusions: Results indicate high cautiousness among Health Care Professionals in judging medical conditions and their impact on physical activity during cancer treatment. However, group comparisons show that familiarity and clinical experience with potential contraindications facilitate a confident handling of safety issues, which at best leads to higher levels of physical activity recommendations during cancer treatment.
Gesehen am 27.04.2018